Biopsychosocial approach in studying the personality of women with different smoking behavior during pregnancy - O. K. Kharkova; A. G. Soloviev; J. O. Odland (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The aim of the study was to explore the personality of women with different smoking behavior during pregnancy using a biopsychosocial approach. Women aged 18-38 years who were hospitalized in the maternity hospitals of Arkhangelsk were enrolled to the study. Pregnant women were divided into three groups depending on the tobacco history: “smokers”, “quitters” and “non-smokers”. As a result of the study, we determined variation in social, biological and psychological components of the personality of women with different smoking behavior during pregnancy. Thus, quitting smoking during pregnancy was more common in married women, and those who had a non-smoking father of the child. Women who stopped smoking during first trimester in compared to smokers were more introverted, had more frequently an instinct of “self-preservation” and “research”. Values of euphoric type of psychological component of gestational dominant and self-esteem were higher among women who stopped smoking during pregnancy in compared to smokers. Smokers in compared to non-smokers had a lower social and economic status, were more often extroverted, emotionally unstable, rigid, less often had a strong development of the instinct «procreation», «research», «altruism», but more often «liberty». Moreover, smokers showed higher rates of depressive, anxious of psychological component of gestational dominant and weaker development of self-esteem and will. So, the revealed features demonstrate those targets to which preventive measures should be directed.